Politeness Maxims Used in English Classroom Interaction of Fourth Semester at STKIP Taman Siswa Bima - Ningsi, Fitri; Nurbaya, Nurbaya; Irawati, Ika; Nurhidayat, Nurhidayat (STKIP Yapis Dompu, 2022)
The The aims of this research is to find out the used types of politeness maxims and the function of most dominant type of politeness maxims used in English classroom interaction during the learning process. The reason why the researcher did this research because the research wanted to provide more sources or references about the types of politeness maxims and the function of most dominant type of politeness maxim that was hopefully be useful for the institution where the researcher study, for other students, other researchers, or readers in general. This research used descriptive qualitative method. Descriptive qualitative method is intended to describe everything related to the type of politeness maxims in classroom interaction. There were three videos which used as a source of data. Those videos showed the activity of the learning process in the classroom interactions. In collecting the data, the researcher would transcribe the videos into written data accurately and classify the data based on types of politeness maxim in order the data would be easily in identified and analyzed. After all the data collected, the researcher analyzed the data and drawed the conclusion. The results of this research can be seen as follows: (1) There were 96 data of politeness maxim appeared in 3 of videos, which consist of 68 data of tact maxim, 14 data of approbation maxim, 10 data of agreement maxim, 2 data of sympathy maxim, 1 data of generosity maxim and 1 data of modesty maxim. (2) Based on the research, tact maxim was the dominant type and the function that can be concluded for several function as declarative, interrogative, imperative and apology function that appeared during the learning process to espouse the spirit of students with the factor of context of situation and participant.